Complex Form Variant of Dysembryoplastic Neuroepithelial Tumor of the Cerebellum. (5th September 2012) - Vaquero, Jesús; Saldaña, Cristobal; Coca, Santiago; Zurita, Mercedes
Abstract : Dysembryoplastic neuroepithelial tumor (DNT) is a benign neoplasm with typical supratentorial location, but the possibility of these rare tumors can also be located in the posterior fossa must be taken into account. We report a 21-year-old woman that suffered gait instability, headache, and diplopia. On CT-scan, an intraparenchymatous cerebellar tumor was disclosed. It was isodense, showing light enhancement after contrast administration. On MRI (T1-weighted image) the tumor was isointense, showing inhomogeneous hyperintensity after-gadolinium administration. On T2-weighted MRI, the tumor was inhomogenously hyperintense. At surgery, a solid and hypervascularized tumor was completely removed. Two years after surgery, the patient is symptom-free. Pathological study showed coexistence of areas of pilocytic astrocytoma with areas in which small rounded oligodendrocyte-like cells (OLC), with strong synaptophysin expression were identified. These neurocytic areas showed an eosinophilic matrix forming microcysts, and cells with aspect of "floating neurons" were occasionally identified. A complex form variant of DNT was diagnosed. Our case suggests that in presence of a cerebellar tumor with features of pilocytic astrocytoma, the possibility of a complex form variant of DNT should be considered.